Design and Development of Automated Indoor Farming with Alert System - Chua Y.L.; Bharuddin S.M.F.M.; Koh Y.Y. (Semarak Ilmu Publishing, 2024)
Indoor farming is becoming an addition to conventional farming practices. This project focused on designing a new, multilevel automated aeroponics system. This newly designed prototype includes an alert system that can alert the user at low water tank levels. The proposed multilevel aeroponic was tested for suitability for maximum plant growth configurations. The prototype development consists of several phases: primary structure, plastic container, water piping, and system setup. Various experiments were conducted within five weeks. The configurations involve changing lighting hours and irrigation patterns. The project's outcome shows the configuration with 12 hours of lighting and a 20-minute misting cycle provides maximum growth. A few recommendations such as lightning setup, user control and misting cycle were also discussed. 2023, Penerbit Akademia Baru. All rights reserved.